Implementation Of Standard Minute Value (SMV) to Achieve Bra Production Target at PT Globalindo Intimates - Shasna Aziizah Atsilia; Dessy Isfianadewi (Publikasi Indonesia, 2025)
Standard Minute Value (SMV) is a method for measuring the standard time for completion of a production process in achieving production targets in accordance with a predetermined plan. In this research, analysis related to SMV was carried out at PT Globalindo Intimates, which is a garment industry manufacturing company whose products are underwear or women's underwear. This research aims to determine the strategies and challenges in implementing SMV to achieve bra production targets. Data collection techniques were carried out using observation, interviews and documentation. Based on the research that has been carried out, the strategy used to implement SMV can be in the form of research to determine the level of difficulty in the production process and observation to see problems in the production process because each type of bra has a different level of difficulty. Factors that cause production targets to not be achieved are unplanned absences, operator skills, machine problems, and human error.